Renal arteriovenous malformation: an unusual cause of recurrent haematuria - Ali, Mazhar (BMJ Publishing Group, 2013)
A 54-year-old woman presented with gross painless haematuria. Initial workup showed no abnormality except mild hydronephrosis on CT scan. Cystoscopy and retrograde pyelography did not find any gross lesion and her urine cytology was also negative. She had recurrent haematuria so her CT was reviewed with the radiologist with clinical suspicion of arteriovenous malformation (AVM) which was suggested by relatively increased contrast density in the hemiazygous vein and renal vein in the arterial phase. She underwent angioembiolisation of left renal AVM after which her haematuria settled.